Toleransi dalam keberagaman: mewujudkan kehidupan damai di indonesia - Najid, Najwa Arina Dinalhaq (Maliki Interdisciplinary Journal, 2025)
The importance of tolerance in maintaining a peaceful life in the midst of ethnic diversity, religion, race, and culture in Indonesia. Tolerance is understood as an attitude of respect and respect for differences, as well as the main foundation in strengthening national unity. Supporting factors The creation of tolerant attitudes includes multicultural education, inclusive religious understanding, the role of community leaders, and government policies that encourage social inclusion. Meanwhile, intolerance, fanaticism, and social inequality are the main challenges that need to be overcome. Education, the media, religious leaders, and the government have a strategic role in instilling the values ​​of tolerance to the community. The strategies offered include strengthening character education, socializing multiculturalism values, and the use of local wisdom. With the collaboration of various parties, it is expected to create a harmonious and mutually respectful society in diversity.